International Licensing and the Strengthening of Intellectual Property Rights in Developing Countries - Park, Walter G.. (OECD Trade Policy Papers, 2004)
This study presents an empirical analysis of the extent to which stronger intellectual property rights promote international technology transfer through licensing activities. The analysis focuses on licensing activities of U.S. multinationals as well as on international licensing alliances between firms in developing and developed nations. Both aggregate level data and firm level data are examined. The study provides general support for the proposition that the strengthening of intellectual property rights - as measured by selected indicators - has had a net positive effect on technology transfer via licensing during the 1990s. The general implication of this study for developing economies is that IPR reform should be one part of a general strategy for promoting economic development in combination with other complementary policy reforms. In particular, patent rights and effective enforcement can be instrumental in enabling firms in developing nations to access and exploit technologies and know-how through licensing agreements with parties in developed nations. Overall, the analysis presented here indicates that where developing countries have moved to address weaknesses in these areas in recent years, they have tended to experience enhanced access to technology through licensing